PERAN PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MENANAMKAN KARAKTER KESADARAN DAN KEPATUHAN HUKUM BERLALU LINTAS PADA SISWA SMA KRISTEN SATYA WACANA SALATIGA - Lista; Nani Mediatati; Dionisius Heckie Puspoko Jati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of the research is to examine the role of Pancasila education in instilling the character of traffic law awareness and compliance among students at SMA Kristen Satya Wacana Salatiga. The research type is qualitative. The subjects of the research are Pancasila education teachers and students of SMA Kristen Satya Wacana. Data collection techniques include observation, interviews, documentation, and questionnaires, and the data is analyzed qualitatively. The research findings indicate that the role of Pancasila education in instilling the character of traffic law awareness and compliance among students at SMA Kristen Satya Wacana meets the criteria for good teaching, including aspects of learning material, presentation, process, social environment, and learning outcomes. The level of traffic law awareness among students, measured by legal knowledge, understanding of the law, attitudes towards the law, and legal behavior, is categorized as good.